From Local to Global: The Internationalization Process of SMEs Based on the Uppsala Model (A Case Study of Atika Shuttlecocks) - Agus Salim; Sudarmiatin Sudarmiatin; Heri Pratikto (Business and Investment Review, 2026)
This study aims to analyze the internationalization process of Small and Medium Enterprises (SMEs) through a case study of Atika Shuttlecocks using the Uppsala Model framework. The research adopts a qualitative approach with a case study method, where data were collected through in-depth interviews with the business owner and supported by secondary data from relevant academic literature. Data analysis was conducted using thematic analysis based on the components of state aspects, change aspects, and network within the Uppsala Model. The findings reveal that the internationalization process occurs progressively through the development of market knowledge and market commitment, which are acquired through direct interactions with international buyers. In addition, marketing activities via social media function as current activities that drive commitment decisions, particularly in terms of product adaptation and business strategy adjustments. The study also finds that digital networks, especially social media platforms, play a significant role in accelerating access to international markets and reducing barriers to expansion.Furthermore, the results indicate that SME internationalization does not fully follow the incremental pattern proposed in the traditional Uppsala Model. Instead, it reflects a combination of gradual learning processes and opportunity-driven expansion facilitated by digital networks. This study contributes to the literature by enhancing the understanding of SME internationalization dynamics in the digital era, particularly by integrating traditional and contemporary perspectives on global market expansion.